Media Convergence Practices and Production in Ghana And Nigeria: Implications for Democracy and Research in Africa - Fosu, Modestus; Ufuoma, Akpojivi (Journal of Applied Journalism & Media Studies, 2015)
In this era of globalization, information accessibility is becoming crucial to empower citizens in their political, economic and sociocultural engagements. In emerging democracies, economic, cultural and political factors have hindered and still hinder the vast majority of the population from inclusion in the media and democratic discourse. Nevertheless, a ‘new’ phenomenon of media convergence is evolving in emerging democracies like Ghana and Nigeria that appears to provide platforms for wide citizen participation in the political and social discourse. From a phenomenological and exploratory perspective, this paper presents an overview of the media convergence practices in newsrooms in Ghana and Nigeria and their potential impact on the countries’ democracy. The article, on the one hand, juxtaposes this new trend against the need for the media to play a crucial role in sustaining and developing democracy in such countries, and on the other hand it opens discussions and research enquiry into the practices and genre underlying such media productions.
Research Article
Keywords: Media Convergence Practices, Production, Ghana And Nigeria, Democracy, Africa